Pengaruh Struktur Modal, Pertumbuhan Aset dan Likuiditas terhadap Profitabilitas (Studi pada Perusahaan Pertambangan yang Terdaftar Di BEI) - Nanik Sisharini; Maria Helena Roswita (Business Management Research, 2023)
The purpose of this study was to determine the effect of capital structure, asset growth and liquidity on the profitability (ROA) of mining companies listed on the Indonesian Stock Exchange. All mining companies listed on the Indonesia Stock Exchange are the research population. Sampling used the purposive sampling technique and obtained 36 mining companies as samples. Data analysis used multiple linear regression with the help of the SPSS program. The results of the study show that sapital structure partially has a non-significant negative effect on profitability. Asset growth has a significant positive effect on profitability, and liquidity has an insignificant positive effect on profitability. Companies need to maintain liquidity and develop assets as an indication of growth to increase profits.